2022
DOI: 10.1007/s00127-022-02332-9
|View full text |Cite
|
Sign up to set email alerts
|

Pet ownership, loneliness, and social isolation: a systematic review

Abstract: Purpose Several publications explored a relationship between pet ownership and lower levels of loneliness and social isolation. However, to the best of our knowledge, no systematic review has yet synthesized the evidence on these associations. Thus, this systematic review aims to evaluate the findings regarding the relations between pet ownership, loneliness, and social isolation. Methods PubMed, CINAHL, and PsycInfo were searched in January 2022. Observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 52 publications
1
39
0
Order By: Relevance
“…Furthermore, conflicting results on the association between pet ownership and mental health have been reported [ 16 20 ]. A systemic review by Kretzler et al revealed that the most profound discrepancies were between qualitative studies and quantitative studies [ 19 ]. The findings of two mixed-methods studies also support the notion that beneficial effects of pets on mental health were observed in qualitative investigations more often than in quantitative ones [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, conflicting results on the association between pet ownership and mental health have been reported [ 16 20 ]. A systemic review by Kretzler et al revealed that the most profound discrepancies were between qualitative studies and quantitative studies [ 19 ]. The findings of two mixed-methods studies also support the notion that beneficial effects of pets on mental health were observed in qualitative investigations more often than in quantitative ones [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Owning pets can increase both perceived and actual social support, as well as facilitating social capital (e.g., connectivity between people), indicating that those with pets may have larger support networks than those who are not pet owners (Wood et al, 2014 ). Indeed, a systemic review of the relationship between pet ownership, loneliness, and social isolation found that owning a pet was associated with lower levels of social isolation and that after the outbreak of COVID-19 pet ownership contributed to lower levels of loneliness (Kretzler et al, 2022 ). While pet ownership alone may provide benefits, the degree of attachment to pets may also contribute to a sense of social support.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a survey conducted in 2021–2022 in the USA, about 70% households (i.e. 90.5 million families) owned a pet, specifically 45.3 million cats and 69 million dogs, with a total pet industry expenditure of $123.6 billion [ 42 , 43 ]. Apart from the growing domestic dog and cat population (estimated around 900 million and 600 million, respectively), a large portion of this number is represented by wild and feral animals, which make up to more than half of the total number [ 21 , 44 ].…”
Section: Greta and Valma Are Top Predator...mentioning
confidence: 99%